The independence of judiciary system and its protection: A study according to Shariah and The Libyan Constitution / Sabah Farag Saad Madi - Sabah Farag , Saad Madi (2017)
If justice is the foundation of authority then the independence of judiciary is the foundation of justice. Full independence of judiciary means that the interference in the judiciary work is not allowed whether from a political or administrative authorities and there is no authority over them except the law. Therefore, the problem in this research in confined in the misunderstanding of the true meaning of the judiciary independence and the type of justice that the judges are required to accomplish. Moreover, the research states the obstacles that are faced and still faced by judiciary independence whether in the stage (during) of the Islamic legislation or in the Libyan law, as well as the loss of the constitutional control over Libyan law. The temporary constitution that came into force after the revolution of the 17th Feb 2011, did not discuss the importance and the necessity of making the judiciary fully independent, equally important, the constitutional guarantees for the independence of judiciary were not enough to ensure the liberty of the judiciary in Libya, particularly, the law of ousting the judge. This research aims to clarify the concept of the judiciary independence from different perspectives according to the rules of justice. It aims also to highlight the role of the constitution as an important means for the independence of judiciary and the way on how to protect it in the Libyan law as well as in the Sharia law, and make a comparison between them. This research will show the role of the constitution as an important guarantee and will investigate the insufficiency of the temporary constitution after the 17th Feb revolution, This is by amending some of the articles at least to ensure some of the judge’s rights. The researcher used the inductive method to clarify the notion of the judiciary independence in Sharia and the Libyan law in order to derive the overall results. The researcher also benefited from the historical approach to employ the historical point views regarding the judiciary independence and then we used the analytical approach to analyze and to comment on the scientific article, texts, views from the Fiqh stand point and the law towards the judiciary independence. The researcher found that the independence of the judiciary under the constitutional protection is a basic condition to achieve justice, and the judiciary in the era of Prophet Muhammad, peace be upon him and later Caliphs and the four imams was independent. Also, the independence of the judiciary in Libya lacks all properties and independent guarantees such as the lack of separation between the authorities. In addition, the Libyan interim constitution which was issued by the National Transitional Council after the revolution of February 17, 2011 didn’t maintain achievement of both freedom and independence of the judiciary, and it didn’t clearly state that the judges cannot be removed. There is no doubt that researching in this topic from these points of views will contribute to the scientific research and the Sharia law as well as the Libyan law in current era.